Scheduling of irrigation for sugarcane (Saccharum officinarum) - GUPTA, RAJENDRA; TRIPATHI, S K (The Indian Journal of Agricultural Sciences, 2013)
Irrigation schedules developed basis of on the mean weather data of 30 years from 1965-95 for predominent sugarcane (Saccharum officinarum L.) growing locations of India indicate that the highest number of irrigations (20) and amount of water (2 643 mm) are required at Ganganagar and Rajkot respectively, whereas lowest number of irrigations (3) and amount of water (303 mm) are required at Cochin. Highest water-use efficiency of 2 221 kg/ha-cm has been observed at Cochin and the lowest (175 kg/ha-cm) at Indore. For higher sugarcane yield and sugar recovery, the optimum share of sugarcane in net irrigated area of the state was found to be 15%.